KAJIAN PENERAPAN PHT DALAM PELESTARIAN LINGKUNGAN PADA PETANI PADI SAWAH DI KABUPATEN BOLAANG MONGONDOW TIMUR - Arfa ., Dondo; Max ., Tulung; Edy F. Lengkong (AGRI-SOSIOEKONOMI, 2016)
ABSTRACT This study aims to determine how the behavior of farmers in the implementation of Integrated Pest Management (IPM) in terms of three aspects: the ecological aspects, economic aspects and technological aspects. This research was conducted in two districts in East Mongondow Bolaang. Collecting data in this study conducted at 40 farmers of the District Parent and Modayak Modayak West. All farmers are farmers who have participated in the Field School of Integrated Pest Management. The data collection is done by using a questionnaire. The questionnaire was prepared based on measurement principles Likert Scale. The collected data were analyzed using Multiple Linear Regression Analysis. Based on the research, regression equation: Y = 4.240 + + 0,326X3 0,083X2 0,07X1 + e. Furthermore, based on the results of testing of the F-statistic can be concluded that the ecological aspects, economic aspects and technological aspects together have the same effect on the opinion of the farmer (Y) significantly. This we can see where the F-count is 8,040 and the F-table for 2866, in other words 8,040 F count> F-Table 2866. So the null hypothesis is rejected. It means ecological aspects, economic aspects and technological aspects together have the same effect on the opinion of the farmer (Y). While based on t-test statistics for independent variables namely the ecological aspects, economic aspects and aspects of the technology are as follows: the ecological aspect t calculate equal to 2,422> t table 2028, the economic aspect t calculate equal to 2,083> t table 2,028 and technological aspects t of 2,702> t table 2,028. Thus, ecological aspects, economic aspects and technological aspects of the real effect on the opinion of farmers about IPM.